Guidelines on the Promotion of Green Jobs in Forestry - Commission économique pour l'Europe des Nations unies (United Nations, 2021)
This publication is intended to assist stakeholders in the forestry sector to successfully navigate the transition to a forest sector that is fully engaged in the green economy. New and increasing opportunities for providing forest-based services and products, growing business and revenue as well as creating jobs arise from this transition. Application of the guidelines will assist in ensuring that the forestry workforce is fit for purpose and forestry is able to attract workers in the 21st century’s labour market.